Patient‐reported outcome measures following soft‐tissue grafting at implant sites: A systematic review. (12th October 2021) - Stefanini, Martina; Tavelli, Lorenzo; Barootchi, Shayan; Sangiorgi, Matteo; Zucchelli, Giovanni
Abstract: Objectives: To review the available literature on patient‐reported outcome measures (PROMs) following soft tissue augmentation at implant sites. Materials and Methods: A comprehensive electronic and manual search was performed to identify clinical studies that involved soft tissue augmentation around dental implants and reported PROMs, including post‐operative morbidity, painkillers intake, quality of life, aesthetics and satisfactions. Results: Nineteen articles were included in the qualitative analysis. Autogenous grafts (free gingival graft and connective tissue graft), acellular dermal matrix and xenogeneic collagen matrix were utilized, either with a bilaminar‐ or an apically positioned flap approach. PROMs reported in the literature included perceived hardship of the procedure and pain during the surgery, post‐operative morbidity, painkillers intake, number of days with discomfort, satisfaction, aesthetic evaluation, quality of life and willingness to undergo the treatment again. Most of the included studies showed similar PROMs between autogenous grafts and substitutes, in terms of post‐operative morbidity, painkillers intake, quality of life, aesthetic assessment and satisfaction. Nevertheless, a trend towards lower post‐operative discomfort was observed for graft substitutes. High scores for patient satisfaction and aesthetic evaluation were observed in all the interventions compared to non‐grafted sites. Conclusions: PROMs represent a crucial endpoint of clinical studies evaluating the outcomes of soft tissue grafts at implant sites. Most of the studies did not find significant differences in terms of patient morbidity and painkillers between autogenous grafts and substitutes. Soft tissue grafting can enhance patient satisfaction and aesthetic evaluation compared to non‐grafted sites.